2017
DOI: 10.1007/s12033-017-0034-7
|View full text |Cite
|
Sign up to set email alerts
|

A Concise Review of MicroRNA Exploring the Insights of MicroRNA Regulations in Bacterial, Viral and Metabolic Diseases

Abstract: MicroRNA (miRNA) is a small section of ribonucleic acid (RNA) that reduces the protein formation by making the pair of the complementary piece of mRNA. The genes of miRNA are present as transcriptional or polycistronic units in the chromosomes. The cellular multiplication, separation and existence like the multitude of genetic functions are affected by miRNA. Nearly 50% of identified miRNA are located in the residence in the intronic part of the genes. The mature miRNA is yielded in two steps. Drosha and RNA-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…As the disease progresses more severely in the patients with early-onset disease, it is likely that the mean serum IL-17A levels are likely higher in these patients. miRs usually bind to the 3'UTR region on the target mRNA, causing either the degradation of the mRNA sequence or an inhibition of its translation [5]. Previous studies have evaluated the levels of miR-1266, miR-340 and miR-197, which are thought to act via IL-17A in patients with psoriasis [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the disease progresses more severely in the patients with early-onset disease, it is likely that the mean serum IL-17A levels are likely higher in these patients. miRs usually bind to the 3'UTR region on the target mRNA, causing either the degradation of the mRNA sequence or an inhibition of its translation [5]. Previous studies have evaluated the levels of miR-1266, miR-340 and miR-197, which are thought to act via IL-17A in patients with psoriasis [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…miRs, a member of the non-coding RNA group which have important regulatory roles in cell type identification and cell differentiation. Several studies have implicated miRs in the pathogenesis of psoriasis in recent years [4,5].…”
Section: Regulatory T (Treg) Cells Suppress the Immune Activation Viamentioning
confidence: 99%
“…The mature miRNA can bind with the RNA-induced silencing complex (10) and exhibits complementary binding with target mRNAs; therefore, it can inhibit or prevent their translation. Several studies have indicated that miRNAs are involved in almost all pathophysiological processes, including embryonic development, cell differentiation, angiogenesis, tumor formation and damage repair (11).…”
Section: Microrna-15a-5p Induces Pulmonary Artery Smooth Muscle Cell mentioning
confidence: 99%
“…It has been reported that miRNAs participate in the regulation of nearly 60% of human protein-coding genes (Friedman et al 2009 ) and 2654 distinct human mature miRNAs available in miRbase ( https://www.mirbase.org/ ) so far supports the idea that miRNAs are involved in complex regulatory networks. Their role has been established in several pathophysiologies including cancer, autoimmune, and metabolic disorders (Garo and Murugaiyan 2016 ; Naveed et al 2017 ). However, in the past ten years, deep sequencing and miRNA microarray technology have evidenced that during the onset of pathogenic infection the host miRNAs regulate cellular responses (Bruscella et al 2017 ; Zhou et al 2018 ) resulting in signaling and physiological modifications.…”
Section: Introductionmentioning
confidence: 99%